(untitled) (GYMNASIUM, 2009)
The concept of effort specificity during athletic tasks and not only is extremely complex and gave rise in time to numerous discussions and controversies between specialists from the domain, through the multiple aspects that it contains, some elaborated, others less studied but very important by their influence that they have over the motor gesture. During the technical training practices before major competitions it is benefic for the ulterior obtained performance, the creation of a similar context to the competition both from the point of view of the situation constraints but also from the point of view of the social frame in which the training must be done.